ROLE OF SCHOOL NUTRITION EDUCATION IN IMPROVING DIETARY HABITS AND REDUCING OBESITY AMONG ADOLESCENTS: AN ANALYTICAL REVIEW (International Journal of Food and Nutritional Sciences, 2022)
This analytical review examines the role of school nutrition education in improving dietary habits and reducing obesity among adolescents. The review considers research studies published between 2016 and 2021, focusing on the effectiveness of school-based nutrition education programs in promoting healthy eating habits and reducing the prevalence of obesity among adolescents. The review identifies that school nutrition education interventions have the potential to positively impact dietary habits and reduce the prevalence of obesity among adolescents. The review highlights the importance of incorporating evidence-based strategies, such as interactive learning activities and peer support, in designing effective nutrition education programs. Additionally, the review emphasizes the need for collaboration between schools, parents, and healthcare providers to ensure the success of school-based nutrition education interventions. Overall, this review provides important insights into the potential of school-based nutrition education programs as a tool for improving adolescent health and reducing obesity prevalence.